Impact of Environmental Pollution Parameters and Wastewater Handling in Manufacturing Industry - Yudha, Redi; N. Danuputri, Denise (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
PT Uyemura Indonesia is a manufacturing company engaged in four or more wheeled vehicle accessories. This study aims to determine the technical handling of industrial liquid waste, critical parameters that are measured according to waste criteria, and the processing of industrial liquid waste. The heavy metal raw materials used by this company are chrome, nickel and copper. Liquid waste handling at PT Uyemura Indonesia based on the questionnaire sheet obtained 90% categorized as good. Physical parameters such as temperature found a total average value of 30.683ºC fulfilling the requirements under the wastewater quality standard, namely 38 ºC, Total Dissoved Solid, found an average total value of 3,109 mg/L does not meet the requirements to exceed the wastewater quality standard, namely 2000 mg /L, and Total Suspended Solid found an average total value of 14.817 fulfilling the requirements below the wastewater quality standard, which is 200 mg/L. Chemical parameters such as chromium obtained a total average value of 0.1975 mg/L fulfilling the requirements under the wastewater quality standard of 0.5 mg/L, nickel obtaining a total average value of 0.2034 mg/L does not meet the requirements is above the wastewater quality standard, namely 0.2 mg/L, and copper obtained a total average value of 0.2969 mg/L fulfilling the requirements below the wastewater quality standard, namely 2 mg/L. The liquid waste treatment process from the results of observations fulfills the requirements of 100% and there are five stages of processing, namely pre-treatment, primary treatment, secondary treatment, tertiary treatment, and sludge treatment.